Molybdenum Mass Fractions and Isotopic Compositions of International Geological Reference Materials. Issue 2 (5th October 2015) - Zhao, Pei‐Pei; Li, Jie; Zhang, Le; Wang, Zhi‐Bing; Kong, De‐Xin; Ma, Jin‐Long; Wei, Gang‐Jian; Xu, Ji‐Feng
Abstract : The double‐spike method with multi‐collector inductively coupled plasma‐mass spectrometry was used to measure the Mo mass fractions and isotopic compositions of a set of geological reference materials including the mineral molybdenite, seawater, coral, as well as igneous and sedimentary rocks. The long‐term reproducibility of the Mo isotopic measurements, based on two‐year analyses of NIST SRM 3134 reference solutions and seawater samples, was ≤ 0.07‰ (two standard deviations, 2 s, n = 167) for δ 98/95 Mo. Accuracy was evaluated by analyses of Atlantic seawater, which yielded a mean δ 98/95 Mo of 2.03 ± 0.06‰ (2 s, n = 30, relative to NIST SRM 3134 = 0‰) and mass fraction of 0.0104 ± 0.0006 μg g −1 (2 s, n = 30), which is indistinguishable from seawater samples taken world‐wide and measured in other laboratories. The comprehensive data set presented in this study serves as a reference for quality assurance and interlaboratory comparison of high‐precision Mo mass fractions and isotopic compositions. Key Points: Determination of Mo mass fractions and isotopic compositions in a set of reference materials by MC‐ICP‐MS using the double‐spike method. The long‐term reproducibility of δ 98/95 Mo was ≤0.07‰ (2 s ). Provision of data for quality assurance and inter‐laboratory comparison for high‐precision Mo isotope determination.